Structural, spectral, electrochemical and DFT studies of two mononuclear manganese(II) and zinc(II) complexes. (28th January 2017) - Chai, Lan-Qin; Tang, Li-Jian; Chen, Li-Chuan; Huang, Jiao-Jiao
Graphical abstract: Two mononuclear M(II) complexes were synthesized via complexation of corresponding M(II) acetate withHL1 originally. The spectral data of both complexes were compared with the ligandHL1 . Both complexes were determined by single crystal X-ray diffraction and display similar coordination geometry and have a 2:1 ligand-to-metal ratio. In the crystal structure, complexes1 and2 form a 1-D infinite chain and2 into 3-D supramolecular frameworks. The electronic transitions and spectral features ofHL1 and both complexes were discussed by DFT and TD-DFT calculations. TD-DFT calculations have been carried out on the optimised geometry to further understand the electronic transitions in the UV–Vis spectra of the compounds. Conclusion of the experiment and theoretical calculations indicate the HOMO–LUMO gap of both complexes is narrower thanHL1 . Abstract: Two mononuclear M(II) complexes, [M(L2 )2 ]·CH3 OH (M = Mn(1 ) and Zn(2 ), HL2  = 1-(2-{[( E )-3, 5-dibromo-2-hydroxybenzylidene]amino}phenyl)ethanone oxime), were synthesized via complexation of corresponding M(II) acetate withHL1 (2-(3, 5-dibromo-2-hydroxyphenyl)-4-methyl-1, 2-dihydroquinazoline-3-oxide, H is the deprotonatable hydrogen) originally. During the reaction, the C–N bond in the ligandHL1 is converted into the CNOH group in theHL2 . The spectral data of both complexes were compared with the ligandHL1 . Both complexes were determined by single crystal X-ray diffraction and display similar coordination geometry and have a 2:1 ligand-to-metal ratio. In the crystal structure, complexes1 and2 form an infinite 1-D chain and2 into 3-D supramolecular frameworks. The electrochemical property of complex1 was investigated by cyclic voltammetry. The electronic transitions and spectral features ofHL1 and both complexes were discussed by DFT and TD-DFT calculations. Time dependent DFT calculations have been carried out on the optimised geometry to further understand the electronic transitions in the UV–Vis spectra of the compounds. In addition, the highest occupied molecular orbital (HOMO), lowest unoccupied molecular orbital (LUMO), and HOMO–LUMO gap were also calculated.